2012
DOI: 10.5009/gnl.2012.6.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Peginterferon Alpha Plus Ribavirin in the Routine Daily Treatment of Chronic Hepatitis C Patients in Korea: A Multi-Center, Retrospective Observational Study

Abstract: Background/AimsWe aimed to evaluate the efficacy and safety of peginterferon plus ribavirin for chronic hepatitis C (CHC) patients under real life setting in Korea.MethodsWe retrospectively analyzed the medical records of 758 CHC patients treated with peginterferon plus ribavirin between 2000 and 2008 from 14 university hospitals in the Gyeonggi-Incheon area in Korea.ResultsHepatitis C virus (HCV) genotype 1 was detected in 61.2% of patients, while genotype 2 was detected in 35.5%. Baseline HCV RNA level was ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 34 publications
1
33
0
2
Order By: Relevance
“…[5][6][7]48 However, the SVR rates of Asian HCV-1 patients receiving 48 weeks of PEG-IFN α-2a plus weight-based RBV were higher than those of Western patients. [49][50][51][52][53][54][55] Two studies enrolling East Asian HCV-1 patients in Taiwan indicated that combination With regard to PEG-IFN α-2b plus weight-based RBV for Asian HCV-1 patients, the SVR rates of 48 weeks of treatment were 44%-51%, which was similar to the response rates for Western HCV-1 patients. 47,56,57 One study in the US which enrolled HCV patients from different ethnic groups (Asian, White, Hispanic, and African-American) confirmed that Asian HCV-1 patients had the highest response rates to IFN-based therapy (Table 4).…”
Section: Combination Therapy Of Peginterferon α and Ribavirin In Asiamentioning
confidence: 73%
See 1 more Smart Citation
“…[5][6][7]48 However, the SVR rates of Asian HCV-1 patients receiving 48 weeks of PEG-IFN α-2a plus weight-based RBV were higher than those of Western patients. [49][50][51][52][53][54][55] Two studies enrolling East Asian HCV-1 patients in Taiwan indicated that combination With regard to PEG-IFN α-2b plus weight-based RBV for Asian HCV-1 patients, the SVR rates of 48 weeks of treatment were 44%-51%, which was similar to the response rates for Western HCV-1 patients. 47,56,57 One study in the US which enrolled HCV patients from different ethnic groups (Asian, White, Hispanic, and African-American) confirmed that Asian HCV-1 patients had the highest response rates to IFN-based therapy (Table 4).…”
Section: Combination Therapy Of Peginterferon α and Ribavirin In Asiamentioning
confidence: 73%
“…[5][6][7]48,49,51,52,55,[59][60][61][62] In East Asian HCV-2 patients treated with PEG-IFN α-2a plus weight-based RBV, the SVR rates were comparable for those receiving 24 or 16 weeks of treatment (95% vs 94%, respectively). 59 …”
Section: Hcv Genotype 2/3 Infectionmentioning
confidence: 99%
“…Real life data indicate that SVR rates are usually higher than pivotal studies. Park et al (21) conducted a study in Korea and evaluated the data of 758 patients; they found SVR rate to be 59.6% in all GTs, 53.6% in GT 1, and 71.4% in GTs 2/3. Similar results were obtained in two studies conducted in Argentina and Italy (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Відомо, що високе вірусне навантаження, «складні» генотипи вірусу (1b та 4), високий рівень аланінаміно-трансферази (АлАТ) та розвиток фіброзу печінки значно ускладнюють терапію та погіршують прогноз ефективності лікування [1]. Також є повідомлення про різну відповідь на лікування за схемою пегінтерферон альфа з рибавірином у представників різних етнічних груп [3].Можна припустити, що можливість прогнозування схиль-ності до розвитку захворювання, тяжкості перебігу та роз-витку ускладнень матиме велике значення під час добору індивідуальної та адекватнішої фармакотерапії ХГС й у покращенні якості життя хворих.Сьогодні велике значення приділяється розвитку фарма-когенетики та пошуку генетичних предикторів безпечності та ефективності лікування багатьох захворювань, зокрема ХГС. Наприклад, встановлено асоціацію певних поліморфіз-мів інтерлейкінів (IL28B) із розвитком стійкої вірусологічної УДК 616.36-002.12-085.246.9:575.174.015.3 …”
unclassified
“…Відомо, що високе вірусне навантаження, «складні» генотипи вірусу (1b та 4), високий рівень аланінаміно-трансферази (АлАТ) та розвиток фіброзу печінки значно ускладнюють терапію та погіршують прогноз ефективності лікування [1]. Також є повідомлення про різну відповідь на лікування за схемою пегінтерферон альфа з рибавірином у представників різних етнічних груп [3].…”
unclassified